The Influence of Collaborative Strategic Reading (CSR) Strategy on Students' Learning to Read Comprehension of Explanatory Texts in Class XI SMA Pertiwi 1 Padang - Husni Diana Sangraini; Afnita Afnita (CV. Rayyan Dwi Bharata, 2023)
There are three objectives of this research. First, it describes reading comprehension skills before using Collaborative Strategic Reading (CSR) strategies in learning to read and understand explanatory texts for class XI SMA Pertiwi 1 Padang. Second, it describes reading comprehension skills after using Collaborative Strategic Reading (CSR) strategies on the reading comprehension skills of class XI SMA Pertiwi 1 Padang. Third, analyzing the effect of Collaborative Strategic Reading (CSR) strategy on the reading comprehension skills of explanatory texts of class XI SMA Pertiwi 1 Padang. This type of research is quantitative research with experimental methods. The research design is a one group pretest and posttest design. The population in this study were students of class XI SMA Pertiwi 1 Padang for the academic year 2022/2023, totaling 307 students. Data were analyzed using percentage formula, arithmetic average formula, and t-test. The research instrument was an objective test, namely a test of reading comprehension skills before and after using Collaborative Strategic Reading (CSR).